Problems of Electronic Mortgage Implementation for the Banking Activities - Mukhidin Mukhidin; Achmad Irwan Hamzani (Jurnal Dinamika Hukum, 2022)
Banking credit is a basic need for the community, especially business actors. In the development of Mortgage Rights in Indonesia, the Government provides services including electronically integrated Registration of Mortgage Rights based on the Regulation of the Head of the National Land Agency No. 9 of 2019 and ATR/BPN Ministerial Regulation No. 5 of 2020 concerning Electronic Mortgage Services and / or hereinafter referred to as "HT-el". The problems formulated in this study are first, what are the problems in the implementation of Electronic Mortgage Rights in the banking world? Second, how to solve the problems faced by users of Electronic Mortgage Rights services for the banking world. Problems / obstacles in the implementation of Electronic Mortgage services based on ATR/BPN Ministerial Regulation No. 5 of 2020, which has been implemented simultaneously nationally since July 8, 2020, are many and have become a challenge for Electronic Mortgage Users, especially Land Deed Officials and Creditors The resolution of problems and obstacles faced by Electronic Mortgage Users, especially Land Deed Officials and Creditors, refers to the Technical Guidelines made by the Ministry of ATR / KBPN, April 29, 2020 because basically these problems and obstacles are mostly related to the IT system and the Electronic HT Service server. Users (Land Deed Official and Creditors) must always confirm these IT problems to the Electronic HT service organizer, namely the local Land Office, so that Electronic Mortgage Users, in this case Land Deed Official and Creditors, must be skilled and adequate in using all the tools needed to complete the granting of Mortgage Rights until the Electronic Mortgage Rights Certificate is issued.Keywords: Problematics, Electronic Mortgage, Banking